Atorvastatin: evidence base 15 years later - A. V. Susekov; N. V. Khokhlova (Кардиоваскулярная терапия и профилактика, 2011)
HMG-CoA inhibitors have been widely used in primary and secondary prevention of atherosclerosis for more than 30 years. The evidence base for statins includes dozens of randomized clinical trials (RCT), involving hundreds of thousands patients. According to the results of the latest meta-analyses, reducing low-density lipoprotein cholesterol (LDL-CH) level by 1 mmol/l in statin-treated patients could decrease cardiovascular risk by 0,8 %. Atorvastatin (Liprimar®) is a modern synthetic statin, which has been thoroughly studied in several RCTs over the last 15 years. These trials demonstrated its effectiveness and tolerability in patients with chronic coronary heart disease, acute coronary syndrome (ACS), Type 2 diabetes mellitus, and arterial hypertension. In the studies comparing atorvastatin (10-80 mg/d) to other statins, baseline LDL-CH levels were reduced by 53 % in atorvastatintreated patients. Atorvastatin therapy was also well tolerated. Compared to placebo, atorvastatin therapy in the dose of 10 and 80 mg/d was associated with the incidence of hepatic transaminase elevation of 0,1 % and 0,6 %, respectively. This evidence base (in particular, the results of the trials on 80 mg/d atorvastatin therapy in ACS patients) has been a cornerstone of modern clinical guidelines, recommending target LDL-CH levels of 2 mmol/l. Currently, atorvastatin is the most widely prescribed statin in the majority of both developed and developing countries. Increasing initial dose and prescribing high-dose atorvastatin therapy (40-80 mg/d) could facilitate an improvement in treatment quality and a reduction in high levels of cardiovascular mortality inRussia.